2018
DOI: 10.1109/lra.2018.2856264
|View full text |Cite
|
Sign up to set email alerts
|

Getting to Know Your Robot Customers: Automated Analysis of User Identity and Demographics for Robots in the Wild

Abstract: Long-term studies with autonomous robots "in the wild" (deployed in real-world human-inhabited environments) are among the most laborious and resource-intensive endeavours in Human-Robot Interaction. Even if a robot system itself is robust and well-working, the analysis of the vast amounts of user data one aims to collect and analyse poses a significant challenge. This paper proposes an automated processing pipeline, using state-of-the-art computer-vision technology to estimate demographic factors from users' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In addition to this aspect, the time for tasks to be performed by a robot is shorter and cheaper [119] and, for this reason, one of the greatest social concerns has to do with the risk of human unemployment caused by robots [13,121] and/or AI [24]. Other relevant social concerns are related to privacy [11,113], data protection [122] or ethical issues [119], which can hinder the implementation of social robots. For example, when robots are used 24 h a day, 7 days a week, in an environment for many weeks, they acquire a significant amount of data from users during social interaction, a situation that is difficult or almost impossible to avoid [122].…”
Section: Resume Of Relevant Categories Main Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this aspect, the time for tasks to be performed by a robot is shorter and cheaper [119] and, for this reason, one of the greatest social concerns has to do with the risk of human unemployment caused by robots [13,121] and/or AI [24]. Other relevant social concerns are related to privacy [11,113], data protection [122] or ethical issues [119], which can hinder the implementation of social robots. For example, when robots are used 24 h a day, 7 days a week, in an environment for many weeks, they acquire a significant amount of data from users during social interaction, a situation that is difficult or almost impossible to avoid [122].…”
Section: Resume Of Relevant Categories Main Authorsmentioning
confidence: 99%
“…Other relevant social concerns are related to privacy [11,113], data protection [122] or ethical issues [119], which can hinder the implementation of social robots. For example, when robots are used 24 h a day, 7 days a week, in an environment for many weeks, they acquire a significant amount of data from users during social interaction, a situation that is difficult or almost impossible to avoid [122]. Aspects related to such concern may be a target for future research.…”
Section: Resume Of Relevant Categories Main Authorsmentioning
confidence: 99%
“…Rich data sets, comprising task and error logs [32], user demographics [36], and navigation failures [15] have been obtained from these deployments, and analysed for the case study for this paper.…”
Section: Trust Loss As a Risk: A Case-studymentioning
confidence: 99%
“…Given that the probability score is only intended to give an indication of the magnitude of a specific failure class, a BoE is most adequate for this assessment. The system data in [36] indicated that there were about 3.5 interactions per operational hour (i.e. time the robot is not resting or charging) with users that are actively using the robot.…”
Section: Trust Loss As a Risk: A Case-studymentioning
confidence: 99%
“…Herrero et al [3] provide a comprehensive analysis of the user base of an autonomous system, which was deployed for long-term operation in a care home, hence studying long-term interaction of an autonomous robotic system. The core contributions of the paper are a processing pipeline to automatically estimate demographics (age, gender) of interacting users, and a model to discriminate between passive interactions (bystanders observing the mobile robot), and active interactions (users directly interacting with the robot).…”
Section: A Interactionmentioning
confidence: 99%